From Cooperation of Parents and Educators Towards Empowering Partnership (Baltic Journal of Sport and Health Sciences, 2014)
Background. Partnership in this thesis is interpreted as the responsibility of children education which is taken by the members and their activity. The main role of the partners is to organize the environment of preschool education for children to use their prior knowledge and experience to understand new information and meaningful context.Methods. Two questionnaires were included in this research, 191 parents and 199 educators were questioned. Results. Educators and parents generally see the purpose of preschool education institution to stimulate the child’s social and cognitive development (88.9%) and considerably rarely the purpose is related to meeting the natural needs of a child (32.2%). Educators more often than parents thought that it was necessary to strengthen the education of parents in partnership with their children’s education (p < .001). Mutual ambition to collaborate (67.3%), better education of parents (49.2%), the maintenance of permanent connection (41.7%), information exchange (49.7%) and better confidence in each other (45.7%) would be helpful in seeking for more effective cooperation.Conclusions. Only a small percentage of parents understand that preschool education is most important to meet the natural needs of children, create healthy situations for the development of children’s inborn inclinations. Educators are not reoriented enough to the tendencies of nowadays and only one third of them believe in its importance to meet the natural needs of a child. In most cases parents and educators indicated the same factors which might influence empowering of parents and educators for the education cooperation which would develop into to partnership, but the importance of the  factors was often different.Keywords: empowering, cooperation, communication, preschool education, partnership.